2017
DOI: 10.3390/nu9020126
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns of European Children and Their Parents in Association with Family Food Environment: Results from the I.Family Study

Abstract: Abstract:The aim of this study was to determine whether an association exists between children's and parental dietary patterns (DP), and whether the number of shared meals or soft drink availability during meals strengthens this association. In 2013/2014 the I.Family study cross-sectionally assessed the dietary intakes of families from eight European countries using 24-h dietary recalls. Usual energy and food intakes from six-to 16-year-old children and their parents were estimated based on the NCI Method. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
87
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(104 citation statements)
references
References 54 publications
(67 reference statements)
7
87
1
5
Order By: Relevance
“…Our hypothesis that the eating habits of mothers and adolescents are similar was supported by our finding that adolescent breakfast skipping was significantly associated with maternal eating habits. The current literature highlights the important role mothers play in influencing their children's eating habits, either positively by providing healthy food and encouraging healthy eating habits or negatively by skipping meals, thereby setting a bad example (Draxten et al, ; Giovannini et al, ; Hebestreit et al, ; Pearson, Williams, Crawford, & Ball, ; Winkler et al, ). Our findings are consistent with earlier research that confirms this maternal influence over adolescent eating habits (Loth, MacLehose, Larson, Berge, & Neumark‐Sztainer, ; Schnettler et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our hypothesis that the eating habits of mothers and adolescents are similar was supported by our finding that adolescent breakfast skipping was significantly associated with maternal eating habits. The current literature highlights the important role mothers play in influencing their children's eating habits, either positively by providing healthy food and encouraging healthy eating habits or negatively by skipping meals, thereby setting a bad example (Draxten et al, ; Giovannini et al, ; Hebestreit et al, ; Pearson, Williams, Crawford, & Ball, ; Winkler et al, ). Our findings are consistent with earlier research that confirms this maternal influence over adolescent eating habits (Loth, MacLehose, Larson, Berge, & Neumark‐Sztainer, ; Schnettler et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…While the literature indicates that both mothers and fathers influence their children's eating behaviors (Ferris et al, ; Robinson, Rollo, Watson, Burrows, & Collins, ), some authors believe mothers have the greater influence in determining the quality of nutrition and dietary habits of adolescents (Schnettler et al, ; Winkler et al, ). This could be explained by the findings of Hebestreit et al () that suggest that mothers are more likely to follow dietary guidelines. In another study, maternal perceptions of the importance of breakfast intake were found to influence how children perceived the value of breakfast (Ali, Razeq, Alnuaimi, & Alzoubi, ).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…To the authors' knowledge, this is the first study to report the associations between parents/caregivers support for healthy eating, home food environment, and family meals with the Brazilian Food Pyramid groups' intake in a sample of under-served girls in Brazil. Further studies should be able to describe how the home food environment (operationalized as the number of shared meals, the availability of core and non-core food items at home, and parents/caregivers support for healthy eating) mediates the association between adolescents dietary intake [31].…”
Section: Discussionmentioning
confidence: 99%
“…195 assessed using a web-based 24-hour dietary recall (24HDR) assessment program, called the "Self-Administered Children, Adolescents and Adult Nutrition Assessment" (Hebestreit et al, 2017). The software was based on the 'Self-Administered Children and Infant Nutrition Assessment' (SACINA), which is considered to be a well-validated method to assess dietary intake (Börnhorst et al, 2014;Hebestreit et al, 2014).…”
Section: Dietary Information and Dietary Analysis Dietary Intake Of mentioning
confidence: 99%